Anti-tumour-promoting and thermal-induced protein denaturation inhibitory activities of β-sitosterol and lupeol isolated from Diospyros lotus L. Issue 10 (18th May 2016) - Rauf, Abdur; Uddin, Ghias; Khan, Haroon; Raza, Muslim; Zafar, Muhammad; Tokuda, Harukuni
Abstract : In this study, the anti-tumour-promoting and thermal-induced protein denaturation inhibitory activities of β-sitosterol (1 ) and lupeol (2 ), isolated from Diospyros lotus L., were explored. Compound1 showed a marked concentration-dependent inhibition against 12- O -tetradecanoylphorbol-13-acetate (20 ng/32 pmol)-induced Epstein–Barr virus early antigen activation in Raji cells with IC50 of 270 μg/ml, without significant toxicity (70% viability). Compound2 showed significant anti-tumour-promoting effect with IC50 of 412 μg/ml, without significant toxicity (60% viability). In heat-induced protein denaturation assay, compound1 exhibited a concentration-dependent attenuation with a maximum effect of 73.5% at 500 μg/ml with EC50 of 117 μg/ml, while compound2 exhibited a maximum effect of 59.2% at 500 μg/ml with EC50 of 355 μg/ml. Moreover, in silico docking studies against the phosphoinositide 3-kinase enzyme also show the inhibitory potency of these compounds. In short, both the compounds exhibited a marked anti-tumour-promoting and potent inhibitory effect on thermal-induced protein denaturation. Abstract :